Pengaruh Program Rumah Pintar Pemilu terhadap Partisipasi Politik Masyarakat pada Kantor Komisi Pemilihan Umum Kota Medan - Zega, Milan Alfianni; Muda, Indra; Batubara, Beby Masitho; Suharyanto, Agung (PERSPEKTIF, 2018)
Aim and scope that research is namely whether the election smart home program has an influence on community political participation (case studies at the Medan city electoral commission office), and to find out whether election smart home programs have an influence on community political participation (case studies at the commission office Medan city elections). The form of this study is to use descriptive research with a quantitative approach with the aim of knowing the effect of variable X (free) with variable Y (bound). This research was conducted at the General Election Commission of Medan City. While data collection is done by distributing questionnaires, interviews and observations. The results of the study showed that there was an influence between the electoral smart actions towards public political participation in the General Election Commission of Medan City. This can be seen from the calculation of R-Sqare which is equal to 0.219 or equal to 21.9%, which means that there is a relationship between the Election Smart House variable (X) on the variable Political Participation of the Community (Y). The presence of Election Smart House (RPP) in Medan City is to increase the level of community participation in the city of Medan. With the presence of the Election Smart House (RPP) in the city of Medan, it is expected that the community can come to visit as a form of community participation to answer the low level of community participation.